" SOCIALIZATION OF THE NEW KUHP AND KUHAP TOWARDS THE LAW ENFORCEMENT OF NARCOTICS FOR SMALL-SCALE DEALERS IN PEKAN TANJUNG BERINGIN VILLAGE " - Khairil Fahmi; Roos Nelly; Lela Erwany; Muhammad Akbar; Ahmad Suhada (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
Changes to the new Criminal Code ( KUHP) and Criminal Procedure Code (KUHAP) bring shift rules and sanctions in handling case narcotics , in particular for perpetrators who have the status as dealer scale small . Activities devotion This aim For give correct and comprehensive understanding​ about provision law latest as well as enforcement The laws in force in the Pekan Tanjung Beringin Village area . Implementation methods done through counseling , discussion interactive , and dissemination material print . Activity results show existence improvement knowledge participant about difference old and new rules , classification action criminal , as well as rights and obligations moment face to face with legal process . Activities This expected can pressing number circulation narcotics scale small and build awareness law public .